Stages of university digital transformation in studies of foreign researchers - Elena N. Belova; Ekaterina Y. Andryushkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
As a significant part of University 4.0 strategy, digital transformation is currently unfolding along with the trends of internationalization and export of education. These processes actualize the experience of foreign universities on the issue of digital transformation. The aim of the study is to describe and systematize the knowledge about the stages of the university digital transformation as presented in studies of foreign researchers. The authors analyzed researches conducted at universities in Latin America, Spain, and Romania over the past 4 years. In the works studied, digital transformation is understood as a purposefully organized complex process, not limited to digitalization and informatization. The experience of digital transformation at foreign universities allows us to trace a number of directions: development of infrastructure, human capital, innovation and networking with partner organizations. The studied works promote the idea of the uniqueness of digital transformation process for each particular university. The practical significance of the paper is the systematization of knowledge about the stages of digital transformation in the works of foreign scientists.